PPI Long Term Use: Risk of Neurological Adverse Events? - Novotny, Michal; Klimova, Blanka; Valis, Martin (Frontiers in Neurology, 2019)
The purpose of this review study is to reveal a potential threat of one type of such widely used and freely distributed drugs, which are proton pump inhibitors that might be the cause of the onset of both dementia and depression. The authors performed a literature review of available studies on the research topic describing adverse effect of proton pum inhibitors (PPIs) (omeprazole, esomeprazole, lansoprazole, dexlansoprazole, rabeprazole, pantoprazole, dexrabeprazole, ilaprazole). For a long time, PPIs were considered to be completely safe drug substances for both short and long-term use. In recent years, there have been a few contradictory studis of absolute safety, especially in patients, who have long been using PPIs. At a time when depression and dementia are rising in the population, this is a very worrying fact that needs to be highlighted, and which needs to be carefully studied and evaluated, ideally trying to prevent it. The findings of most research studies described in this review indicate that there is a direct association between the onset of dementia and depression on one side and the long-term use of PPIs on the other.